Generation and plans for development of system of ecological and demographic survey and radiation monitoring of rural communities in the Republic of Kazakhstan (Journal of Geography and Environmental Management, 2019)
The article contains description of objectives in designing technical and functional architecture ofthe information system, created for the field and laboratory data processing by ecological and demographicprojects inspection and radiation monitoring of rural communities the Republic of Kazakhstan. The systemdevelopment program includes the information-based analysis and geographic information subsystemdevelopment.